A Comprehensive Framework for Adoption of Mobile Broadband Services in Indian Cities - Mukherjee, Jaydeep (Asian Journal of Empirical Research, 2016)
3G mobile broadband services have not yet picked up in India, while newer 4G technologies like Long Term Evolution are already in pipeline. Mobile network operators in India need to understand the drivers of adoption of new technologies as they have to make large investments. This research developed a comprehensive conceptual framework of mobile technology adoption in India based on literature, which was empirically tested among 276 the early adopters in India. The fit of empirical data the hypothesized model was analyzed using structural equation modeling. The results showed that the impact of social influence on individual’s perception of usefulness and the impact of price on individual’s behavioral intention to adopt was significant, while the impact of perceived risk in use and social influence construct on the individual attitude was not significant.